Prevalence of Methicillin Resistant Staphylococcus aureus in Children - Thapa, Santosh; Pant, D. K.; Ghimire, P.; Thapa, P. B. (Journal of Nepal Health Research Council, 2009)
Not uploaded. Key words: Multidrug resistant; Prevalence; Staphylococcus aureus. DOI: 10.3126/jnhrc.v6i1.2442 Journal of Nepal Health Research Council Vol. 6, No. 1, Issue 12, April, 2008 Page: 38-41